Automated preparation of 2‐[18F]fluoropropionate labeled peptides using a flexible, multi‐stage synthesis platform (iPHASE Flexlab). (29th December 2017) - Haskali, Mohammad B.; Roselt, Peter D.; Hicks, Rodney J.; Hutton, Craig A.
Abstract : Radiolabelled peptides are vital tools used in positron emission tomography imaging for the diagnosis of disease, drug discovery, and biomedical research. Peptides are typically labeled through conjugation to a radiolabelled prosthetic group, which usually necessitates complex, multi‐step procedures, especially for fluorine‐18 labeled peptides. Herein, we describe the automated synthesis and formulation of 2‐[ 18 F]fluoropropionate labeled RGD‐peptides through use of the iPHASE Flexlab as an effective dual‐stage radiochemical synthesis module. The fully automated preparation of the monomeric RGD‐peptides, [ 18 F]FP‐GalactoRGD and [ 18 F]FP‐c(RGDy(SO3 )K), was accomplished in under 90 minutes with n.d.c. radiochemical yields ca. 7% from fluoride. Similarly, the automated preparation of the dimeric RGD‐peptides, [ 18 F]F‐PRGD2 and [ 18 F]FP‐E(RGDy(SO3 )K)2, was accomplished in under 105 minutes with n.d.c. yields ca. 4% from fluoride.